Aluminium-copper-SiCp composite materials corrosion in biodiesel - Maleque, Md. Abdul (Trans Tech Publications, Switzerland, 2012)

(untitled)
The aim of this paper is to investigate the corrosion behaviour of aluminium-copper-SiCp composite materials under palm oil biodiesel (POB). Corrosion behaviour test was performed using both weight loss and polarization methods for two different types of aluminium-copper-SiCp composite materials such as ACM 1(2% Cu, 20% SiC, and 78% Al) and ACM 2 (6% Cu, 20% SiC, and 72% Al). The materials were characterized using scanning electron microscope (SEM) for surface morphology. The results showed that corrosion rate of ACM 2 is higher than ACM 1 in presence of palm oil biodiesel due to the higher amount of copper in the composite which is more susceptible to corrosion. The surface morphology after corrosion test showed that chemical corrosion occurs on the surface due to the dominant of the fatty acid in the POB. Therefore, in this study it can be concluded that aluminium-copper-SiCp composite materials are susceptible to corrosion in biodiesel.